Integration of Financial Accounting and Accounting Information Systems in Supporting Social and Environmental Accounting: A Study in the Public Sector of Mataram City - Syarifah Massuki Fitri; Muhammad Syukri; Suandi (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study examines the integration of financial accounting and Accounting Information Systems (AIS) in supporting social and environmental accounting (SEA) within the public sector. It addresses the limited empirical evidence on how integrated accounting systems contribute to broader accountability beyond financial reporting, particularly in local government contexts in developing countries. Methods – A quantitative approach with a cross-sectional survey design was employed. Data were collected from 200 public sector employees in Mataram City using structured questionnaires. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to examine the relationships among financial accounting–AIS integration, financial accounting quality, AIS effectiveness, and SEA. Findings – The results indicate that financial accounting–AIS integration significantly improves AIS effectiveness (β = 0.36; p < 0.001), while financial accounting quality also has a significant effect (β = 0.41; p < 0.001). AIS effectiveness is positively associated with SEA (β = 0.39; p < 0.001). Financial accounting–AIS integration and financial accounting quality also have significant direct effects on SEA. The model explains 64% of SEA variance. AIS effectiveness partially mediates the relationships between accounting practices and SEA, since the direct effects remain significant. Research Implications – The cross-sectional design and focus on a single local government limit the generalizability of the findings. The use of self-reported survey data may introduce response bias and reflects employees’ perceptions of SEA practices rather than objective disclosure evidence. Nevertheless, the study provides insights into how integrated accounting systems are associated with perceived improvements in sustainability-related reporting. Originality – This study offers an integrative framework that connects financial accounting, AIS, andSEA in a public sector context. It contributes empirical evidence from a developing country and highlights the role of AIS effectiveness as a partial mediating mechanism supporting sustainability-oriented accountability.